Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.402
|View full text |Cite
|
Sign up to set email alerts
|

Towards Emotion-aided Multi-modal Dialogue Act Classification

Abstract: The task of Dialogue Act Classification (DAC) that purports to capture communicative intent has been studied extensively. But these studies limit themselves to text. Non-verbal features (change of tone, facial expressions etc.) can provide cues to identify DAs, thus stressing the benefit of incorporating multi-modal inputs in the task. Also, the emotional state of the speaker has a substantial effect on the choice of the dialogue act, since conversations are often influenced by emotions. Hence, the effect of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Dialogue acts can be predicted both by prosodic and lexical cues, with the latter being more effective [99,101]. Moreover, Saha et al [36] recently investigated the relationship between dialogue acts and text-based emotion recognition using two emotional datasets, one of them IEMOCAP, and found that jointly modelling both can improve emotion recognition performance. They released their dialogue act annotations 3 , thus opening a new avenue of exploration for the interaction between the underlying linguistic content and model performance.…”
Section: Dialogue Act Analysismentioning
confidence: 99%
“…Dialogue acts can be predicted both by prosodic and lexical cues, with the latter being more effective [99,101]. Moreover, Saha et al [36] recently investigated the relationship between dialogue acts and text-based emotion recognition using two emotional datasets, one of them IEMOCAP, and found that jointly modelling both can improve emotion recognition performance. They released their dialogue act annotations 3 , thus opening a new avenue of exploration for the interaction between the underlying linguistic content and model performance.…”
Section: Dialogue Act Analysismentioning
confidence: 99%
“…Emotion recognition is broadly studied with uni-modal (Yang et al 2018;Majumder et al 2019;Saha et al 2020;Jiao, Lyu, and King 2020;Huang et al 2021), bi-modal (Mittal et al 2020b;Liu et al 2020;Zhao et al 2020) and multi-modal (Mittal et al 2020a;Sun et al 2020;Zhang et al 2021a;Lv et al 2021). More effective multi-modal fusion translates to better performance.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, some researchers argue that chatbots should also have such abilities to blend information from different modalities. There are some recent works trying to build multimodal dialogue systems (Le et al, 2019;Chauhan et al, 2019;Saha et al, 2020;Singla et al, 2020;Young et al, 2020), but these systems are still far from mature.…”
Section: Conclusion and Trendsmentioning
confidence: 99%